The Syntactic variation of Spanish dialects - Gallego, Angel J. (New York Oxford University Press, 2019)
" This book offers a comprehensive overview of the syntactic variation of the dialects of Spanish. More precisely, it covers Spanish theoretical syntax that takes as its data source non-standard grammatical phenomena. Approaching the syntactic variation of Spanish dialects opens a door not only to the intricacies of the language, but also to a set of challenges of linguistic theory itself, including language variation, language contact, bilingualism, and diglossia. The volume is divided into two main sections, the first focusing on Iberian Spanish and the second on Latin American Spanish. Chapters cover a wide range of syntactic constructions and phenomena, such as clitics, agreement, subordination, differential object marking, expletives, predication, doubling, word order, and subjects. This volume constitutes a milestone in the study of syntactic variation, setting the stage for future work not only in vernacular Spanish, but all languages. "--Provided by publisher.
Part I. European Spanish -- 1. Differential Object Marking and clitic dubspecification in Catalonian Spanish -- Francisco Ordóñez and Francesc Roca -- 2. Mass / count distinctions in Ibero-Romance dialects -- Inés Fernández-Ordóñez -- 3. Empty Categories and Clitics -- Juan Romero -- 4. Dialectal variation in clitic placement in Andalusian and Asturian Spanish negative infinitival imperatives -- Julio Villa-García -- 5. Polarity questions with fronted foci in the Spanish of the Basque Country -- Aritz Irurtzun -- 6. Causativity in Southern Peninsular Spanish -- Ángel Jiménez-Fernández and Mercedes Tubino-Blanco -- Part II. American Spanish -- 7. Citic doubling in a doubling world. The case of Argentinean Spanish reconsidered -- Ángela Di Tullio, Andrés Saab, and Pablo Zdrojewski -- 8. Syntactic phenomena in Peruvian Spanish -- Miguel Rodríguez-Mondoñedo -- 9. Contrastive focus in Yucatecan Spanish -- Rodrigo Gutiérrez-Bravo, Carlos Martín Sobrino, and Melanie Uth -- 10. Caribbean Spanish and theoretical syntax. An overview. -- Ignacio Bosque and José M. Brucart -- 11. On left-peripheral expletives in Central Colombian Spanish -- José Camacho -- 12. Reportative que in Mexican Spanish -- Esthela Treviño -- Subject Index -- Language Index.
Includes bibliographical references and indexes.
Keywords: Spanish language -- Syntax; Spanish language -- Variation; Spanish language -- Dialects -- United States; Spanish language -- Dialects -- Europe; Spanish language -- Dialectology